Mirror-image aptamer kissing complex for arginine-vasopressin sensing - Chovelon, Benoit; Fiore, Emmanuelle; Faure, Patrice; Peyrin, Eric; Ravelet, Corinne (Analytica chimica acta, 2018)
The recently reported aptamer kissing complex (AKC) strategy has allowed for the development of a new kind of sandwich-like sensing tools. Currently AKC assays have been only applied to low molecular weight molecules and their functionality in complex matrices remains challenging. The objective of the present study broken down into two sub-aims; exploring the propensity to broaden the scope of detectable analytes and designing a more robust system for potential applications to realistic samples. An all L-configuration aptaswitch module derived from a hairpin spiegelmer specific to a larger target, i.e. the arginine-vasopressin (AVP) hormone, was elaborated. The target-induced AKC formation in presence of a specific mirror-image RNA hairpin (L-aptakiss) probe were analyzed by using fluorescence anisotropy. The mirror-image kissing complex was successfully formed when the L-AVP target bound to the engineered L-aptaswitch element. It was also established that the use of methanol as cosolvent significantly improved the assay sensitivity through the stabilization of the ternary complex. Finally, the capability of the mirror-image method to operate in 10-fold diluted, untreated human serum was illustrated. The current work revealed that the AKC concept can be expanded to a wider range of targets and converted to a L-configuration sensing platform especially suitable for bioanalysis purposes. [Display omitted] •The mirror-image aptamer kissing complex (AKC) approach was demonstrated.•The scope of the AKC strategy was extended to peptide targets.•The all-L AKC improved the fluorescence anisotropy assay robustness for complex matrix analysis.•The use of methanol as cosolvent enhanced the assay sensitivity.